Gartenfreund: Exploring the botanical garden with an inclusive app - Birnstiel, Sandra; Steinmüller, Benedikt; Bissinger, Kerstin; Doll-Gerstendörfer, Simone; Huber, Stephan (MuC'19: Proceedings of Mensch und Computer 2019, 2019)
Many museums exclude visually impaired people by offering only visual presentations of exhibition pieces. To improve the experience of the botanical garden in Würzburg for visually impaired people, we conducted a human centered design process with blind self-experiences and contextual interviews with two experts. From the qualitative insights we prototypically designed the inclusive smartphone app Gartenfreund. Gartenfreund consists of an NFC triggered audio guide with precise path descriptions to the next station and an interactive soundscape that produces animal sounds from the canopy level at which the phone is pointed. A preliminary evaluation shows that sighted and visually impaired participants could use the app without any usability problems and that the path descriptions need to be shorter and supported by a tactile orientation system for blind users. Our main contributions are the insights from user research and the inclusive app Gartenfreund. In future work we will iterate the design and conduct a more extensive evaluation involving both blind and sighted users.<br
Keywords: Blind; Inclusive design; Exhibition; Visual impaired users; NFC